Benign Tumors of the Spine: Has New Chemotherapy and Interventional Radiology Changed the Treatment Paradigm?. Issue 20 (15th October 2016) - Charest-Morin, Raphaële; Boriani, Stefano; Fisher, Charles G.; Patel, Shreyaskumar R.; Kawahara, Norio; Mendel, Ehud; Bettegowda, Chetan; Rhines, Laurence D.
Abstract : Study Design: Clinically based systematic review. Objective: To determine the role of (A) medical treatment and (B) interventional radiology as either adjuvant or stand-alone treatment in primary benign bone tumors of the spine. Methods: A multidisciplinary panel of spine surgeons, radiation oncologists, and medical oncologists elaborated specific focused questions regarding aneurysmal bone cyst, giant cell tumor, and osteoid osteoma. Denosumab, bisphosphonate, interferon, bone marrow aspirate, doxycycline, thermal ablation, and selective arterial embolization were identified as areas of interest for the article. A systematic review was performed through MEDLINE and EMBASE. Recommendations based on the literature review and clinical expertise were issued using the GRADE system. Results: The overall quality of the literature is very low with few multicenter prospective studies. For giant cell tumor, combination with Denosumab identified 14 pertinent articles with four multicenter prospective studies. Nine studies were found on bisphosphonates and six for selective arterial embolization. The search on aneurysmal bone cyst and selective arterial embolization revealed 12 articles. Combination with Denosumab, Doxycycline, and bone marrow aspirate identified four, two, and three relevant articles respectively. Eleven focused articles were selected on the role of thermal ablation in osteoid osteoma. Conclusion: Alternative and adjuvant therapy for primary benign bone tumors have emerged. Their ability to complement or replace surgery is now being scrutinized and they may impact significantly the algorithm of treatment of these tumors. Most of the data are still emerging and further research is desirable. Close collaboration between the different specialists managing these pathologies is crucial. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the text